Insights into the role of adipose‐derived stem cells: Wound healing and clinical regenerative potential. Issue 4 (23rd August 2020) - Zou, Ming‐Li; Liu, Si‐Yu; Sun, Zi‐Li; Wu, Jun‐Jie; Yuan, Zheng‐Dong; Teng, Ying‐Ying; Feng, Yi; Yuan, Feng‐Lai
Abstract: The incidence of acute and chronic wound diseases is rising due to various reasons. With complicated pathogenesis, long course, difficult treatment and high disability, wound diseases have become a major burden for patients, their families, and society. Therefore, the focus of research is to identify new ideas and methods for treatment. Fat grafting has gained increased attention because of its effectiveness in wound treatment, and further analysis has uncovered that the stem cells derived from fat may be the main factor affecting wound healing. We summarize the function of adipose stem cells and analyze their possible mechanisms in tissue repair, helping to provide new ideas for the treatment of wound healing. Abstract : Herein, a summary of the function of adipose stem cells and their possible mechanisms in tissue repair, hoping to provide new ideas for the treatment of wound healing is presented.